Burnout resilience in the face of the COVID-19 pandemic - Mucharraz y Cano, Yvette (2025)
The COVID-19 pandemic had an unprecedented negative impact on women’s mental well-being, especially on mothers. This article proposes the concept of “burnout resilience” and introduces “structural support” as a variable that influences job burnout in women, mothers working in executive positions. Different support measures may promote resilience: in this case, the structural, organizational, and family-related. The study focuses on resilience enablers in a disaster scenario like the COVID-19 pandemic. The study highlights the relevance for public policy and organizations of ensuring organizational and structural support that contributes to develop resilience for mitigating burnout, especially during natural catastrophe periods and war environments, among other negative scenarios. The investigation aimed to quantify job burnout among 704 executive mothers during the COVID-19 pandemic, using the Maslach Burnout Inventory General survey. The data-collection method employed was a non-probabilistic snowball sampling technique, and the hypotheses were tested using a comparison of means t-test and one-way analysis of variance (ANOVA). Results showed the relationship between job burnout and organizational, familial, and structural support. The findings also reveal that organizational and structural support attenuated burnout, while familial support is not correlated with burnout mitigation. Moreover, compared to the pre-pandemic period, executive mothers seemed to have experienced an increase in burnout during the COVID-19 pandemic.